PEMBERDAYAAN UMKM BERBASIS TEKNOLOGI INFORMASI: PRODUKSI VIDEO TUTORIAL EKONOMI UNTUK UMKM GEBLEK MAKNYUSS, KULON PROGO, DIY - Jeffry Andhika Putra; I Putu Deny Arthawan Sugih Pabowo; Arum Kurnia Sulistyawati; Surya Tri Atmaja Ramadhani; Ali Muhtar (SWADIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
This community service program aims to address the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in enhancing digital promotion strategies and increasing product appeal. The partner, Geblek Maknyuss MSME, located in Kranggan, Galur, Kulon Progo, Special Region of Yogyakarta (DIY), experienced limitations in digital marketing skills, particularly in producing engaging visual content and effectively utilizing information technology. To overcome these challenges, the program focused on developing audiovisual promotional media and strengthening the product brand identity. The implementation methods included field surveys, participatory discussions, storyboard design, documentation of production processes, video editing, and the creation of printed promotional materials such as logos, banners, standing banners, and stickers. The program’s output consisted of an economic tutorial video showcasing the production process and product branding, along with printed materials that could be used for marketing purposes. This initiative enhanced the partner’s ability to utilize digital platforms for promotion, expanded market reach, and provided students with practical experience in applying academic knowledge. Collaboration between academia and MSME is key to fostering sustainable local economic growth.Program pengabdian masyarakat ini bertujuan mengatasi permasalahan mitra Usaha Mikro, Kecil, serta Menengah (UMKM) dalam meningkatkan strategi promosi digital serta daya tarik produk. Mitra, UMKM Geblek Maknyuss di Kranggan, Galur, Kulon Progo, Daerah Istimewa Yogyakarta (DIY), menghadapi keterbatasan keterampilan pemasaran digital dalam hal konten visual yang kurang menarik serta belum optimal dalam pemanfaatan teknologi informasi. Solusi untuk mengatasi permasalahan tersebut mencakup pembuatan media promosi audiovisual, serta penguatan identitas merek produk. Metode pelaksanaan yang dilakukan meliputi survei lapangan, diskusi partisipatif, perancangan storyboard, dokumentasi proses produksi, penyuntingan video, serta pengembangan media cetak (logo, banner, stand banner, serta stiker). Hasil kegiatan berupa video tutorial ekonomi yang memperlihatkan proses produksi, branding produk, serta media cetak pendukung yang dapat dimanfaatkan dalam kegiatan pemasaran. Program ini meningkatkan kemampuan mitra dalam memanfaatkan platform digital untuk pemasaran, memperluas jangkauan pasar, serta memberikan pengalaman praktis bagi mahasiswa dalam menerapkan ilmu akademik. Kolaborasi antara akademisi serta UMKM menjadi kunci dalam mendorong pertumbuhan ekonomi lokal yang berkelanjutan.